Stereotipe Perempuan Urban dalam novel Kami (Bukan) Fakir Asmara Karya J.S. Khairen - Fatjriani, Anisa; Adek, Muhammad (Persona: Kajian Bahasa dan Sastra, 2023)
The aim of this research is to identify the stereotypes attached to urban female characters and discuss the reactions of urban female characters to the stereotypes attached to the novel Kami (bukan) Fakir Asmara by J.S. Khairen. This research uses Feminist Sociology theory which links the analysis of literary works with social phenomena and realities. This research is literary study with descriptive methods. The data collection technique in this research was managed by reading the novel intensively, identified the data, and taking an inventory of the data into a data collection format. The data analysis technique is carried out through content analysis.Based on the research results, there are five negative stereotypes attached to urban female characters in novels. The purpose of these stereotypes is to give women the opportunity to reduce their movement. The two reactions found were a reaction of approval and a reaction of disagreement. These two reactions prove that the existence and voice of women is an effort to oppose patriarchy which is detrimental to women. These reactions are a symbol that women bravely show their identity.